Talent development model for a career in Islamic banking institutions: A SEM approach - Mohd Ikhwan Aziz; Asyraf Afthanorhan; Zainudin Awang (Cogent Business & Management, 2016)
Presently the Malaysian Islamic banking brand name has surged drastically into the mainstream platform. In the meantime, in order to cope with this situation, Islamic banking institutions (IBIs) require more positions to be filled, currently needing a 200,000 workforce by 2020. However, to date only a 17,621 workforce are available in the IBIs which constitutes 11% of that required. This connection has dragged IBIs to the different dimension of issues that is talent shortage. The effect of the problem has made many Islamic banking education and knowledge service providers (IBEKSP) offer an Islamic banking programme in order to confront the situation. Despite Malaysian IBESKP producing abundant graduates nowadays in the job market, Malaysian IBIs still address the issue that they face a critical shortage of talent. Therefore this article attempts to propose a specific talent development model for Malaysian Islamic banking graduates. These data were evaluated by a group of Malaysian undergraduates regarding talent development current practice in university. This study used a structural equation modelling method and it was found that the proposed variables of the study have a positive impact on talent development.
Keywords: 650